Bayesian Belief Networks: a Tool for Education Use - Торопова, Александра Витальевна (Computer Tools in Education, 2017)
Bayesian belief networks science are a perspective mathematical and software tool for use and study in higher educational institutions because of its clarity and popularity in different scientific research fields. A brief introduction to Bayesian belief network is given, the software systems for working with them are described. Some software systems more popular and famous are described in the details by the example of socially significant behavior model, which is a part of the actual research projects of both students and postgraduates.